Strategic Alliances and the Boundaries of the Firm - Robinson, David T. (Review of Financial Studies, 2008)
[Strategic alliances are long-term contracts between legally distinct organizations that provide for sharing the costs and benefits of a mutually beneficial activity. In this paper, I develop and test a model that helps explain why firms sometimes prefer alliances over internally organized projects. I introduce managerial effort into a model of internal capital markets and show how strategic alliances help overcome incentive problems that arise when headquarters cannot pre-commit to particular capital allocations. The model generates a number of implications, which I test using a large sample of alliance transactions in conjunction with Compustat data.]